International cooperation of Belarusian universities in the field of human rights teaching and research - Shadurski, Victor G. (Journal of the Belarusian State University. International Relations, 2020)
The study is devoted to the analysis of long-term cooperation of Belarusian universities with their Swedish partners in the field of teaching and research on human rights. Using concrete examples, the author shows the most successful forms of Belarusian-Swedish cooperation, which influenced not only the situation in higher education, but also the perception of human rights issues in the Belarusian society as a whole (development of lecture courses, publication of research results, training seminars, exchange of teachers and students). The most notable results have been achieved towards gender equality.
Keywords: Belarus; Sweden; Belarusian State University; Raoul Wallenberg Institute; Belarusian-Sweden relations; Swedish International Development Cooperation Agency; human rights; gender equality